Investigating white matter structure in social anxiety disorder using fixel-based analysis. (November 2021) - Gorman, Ben D.A.; Calamante, Fernando; Civier, Oren; DeMayo, Marilena M.; Demetriou, Eleni Andrea; Hickie, Ian B.; Guastella, Adam J.
Abstract: Social anxiety disorder (SAD) is one of the most common mental health disorders in youth, defined by a persistent and intense fear of negative evaluation by others. Recent research has examined its neurological underpinnings, including structural connectivity changes in the brain. This has been examined through measurement of the white matter (WM) structure of fibre pathways. Previous studies have shown inconsistent results. This study attempts to resolve these inconsistencies by utilising a recently proposed, advanced method for diffusion MRI analysis, known as fixel based analysis (FBA). This technique enables examination of WM macro- and micro-structure with measures of fibre density (FD), fibre bundle cross-section (FC) and fibre density-cross-section (FDC). This study evidenced increased FDC in a region of the right superior longitudinal fasciculus (SLF) from a whole brain FBA, along with increased FC and FDC from an analysis restricted to a-priori tracts of interest, in regions of the right inferior longitudinal fasciculus (R-ILF). The average FDC of the left uncinate fasciculus (L-UF) was also increased. To examine the relationship between WM structure and severity of symptoms, these FBA metrics were correlated with Leibowitz Social Anxiety Scale (LSAS) scores. From the tract-restricted analysis an inverse correlation between FC and LSAS scores was found in the R-ILF. The average FC of the R-ILF was also inversely correlated with symptom severity. By utilising a more sensitive and fibre-specific method of analysis than previous studies, these findings highlight innovative outcomes relating to white matter in numerous fibre tracts.